Physiological plasticity of high-temperature intertidal cyanobacterial microbial mats to temperature and salinity: daily and seasonal in situ photosynthetic performance. Issue 2 (2nd April 2020) - Aguilera, Ángeles; Suominen, Saara; Pétursdóttir, Sólveig; Olgudóttir, Edda; Guðmundsdóttir, Elísabet Eik; Altamirano, María; González-Toril, Elena; Hreggviðsson, Guðmundur Óli
ABSTRACT: The physiological plasticity of five cyanobacteria microbial mats from an extreme high temperature intertidal environment (SW Iceland) was analysed both daily and seasonally. Daily cycles under in situ natural conditions were monitored from June to October using pulse-amplitude modulated (PAM) fluorometry and pigment composition in order to study the photosynthetic performance of these microbial mats in relation to environmental fluctuations linked to irradiance and temperature. In vitro temperature and salinity experiments of photosynthetic responses were also conducted. A total of 10 taxa were identified, the most abundant species being Cyanobacterium sp. and Geitlerinema sp. The microbial mats showed a remarkable photosynthetic adaptation to daily and seasonal changes in temperature and solar radiation. For all microbial mats, rETRmax values decreased from June to October, while Fv /Fm remained constant in terms of absolute values. Although high irradiances during June and July affected photosynthesis through photoinhibition, recovery was observed under high temperatures (between 40–50°C), which supports the hypothesis that temperature is a determining factor in the photosynthetic performance of these cyanobacterial mats. Our results showed a significant increase in the Chl a-b and phycobiliproteins content from June to October, as well as a significant decrease in total carotenoids content.